Superoxide dismutase isoenzymes gene expression in peripheral blood mononuclear cells in patients with coronary artery disease - Ninić Ana (Journal of Medical Biochemistry, 2019)
Background: Coronary artery disease (CAD) is one of the most important causes of mortality and morbidity in wide world population. Dyslipidemia, inflammation and oxidative stress may contribute to disruption of endothelium structure and function, atherosclerosis and CAD. Our study was aimed to determine whether Cu/Zn superoxide dismutase (Cu/Zn SOD) and Mn superoxide dismutase (Mn SOD) gene expression could be modulated by oxidative stress in CAD patients. Methods: This study included 77 CAD patients and 31 apparently healthy persons. Serum lipid levels, high sensitivity C-reactive protein (hsCRP), total antioxidant status (TAS) and thiobarbituric acid-reacting substances (TBARS) were measured. SOD isoenzymes gene expression was determined in peripheral blood mononuclear cells using quantitative polymerase chain reaction. Results: Mn SOD messenger ribonucleic acid (mRNA) levels were significantly lower in CAD patients than in controls (p=0.011), while Cu/Zn SOD mRNA levels did not change significantly between tested groups (p=0.091). We found significantly lower high-density lipoproteincholesterol (HDL-c) (p<0.001) and TAS (p<0.001) levels and significantly higher hsCRP (p=0.002) and TBARS (p<0.001) in CAD patients than in controls. There were significant positive correlations between TAS and Mn SOD mRNA (p=0.243, p=0.020) and TAS and Cu/Zn SOD mRNA (p=0.359, p<0.001). TBARS negatively correlated only with Cu/Zn SOD mRNA (p=-0.215, p=0.040). TAS levels remained independent predictor for Mn SOD mRNA levels (OR=2.995, p=0.034). Conclusions: Results of this study showed that Mn SOD gene expression were decreased in CAD patients compared to controls and can be modulated by nonenzymatic antioxidant status in blood.